Interdependence and Affective Processes in Relational Turbulence Theory. (2nd September 2022) - Quaack, Karly R.; Bolkan, San; Goodboy, Alan K.
Abstract : Studies guided by relational turbulence theory (RTT) emphasize negative emotions as the affective mechanism responsible for turbulence arising from interfering partners. However, a more complete examination of RTT's affective mechanisms should study how interference and facilitation indirectly predict turbulence through intensified negative and positive emotions. We report results from 349 individuals after examining interference and facilitation together to estimate indirect effects on turbulence through negative and positive emotions. Results revealed a positive direct effect of interference on turbulence, and a positive indirect effect of interference on turbulence through negative and positive emotions. We observed a negative indirect effect of facilitation on turbulence through positive emotions. RTT processes originating from interference and facilitation were contrasted and found to be equivalent in strength.